Exogenous application of ascorbic acid and putrescine: A natural eco-friendly potential for alleviating NaCl stress in barley (Hordeum vulgare) - Seleem, Engy Alaa; Ibrahim, Hend Mohammad Saad; Taha, Zeinab Kassem (Emirates Journal of Food and Agriculture, 2021)
A pot experiment was performed in the green house of Agricultural Botany Department, Faculty of Agriculture, Cairo University, Giza, Egypt during the winter seasons of 2019 and 2020 to investigate the effect of exogenous application of ascorbic acid (AsA) and putrescine (Put) in ameliorating the growth parameters of barley (Hordeum vulgare L.) plant under saline conditions (9.3 and 14 dS m-1). Two concentrations of either AsA (100 and 300 ppm) or Put (100 and 200 ppm) were foliar-sprayed individually or in combination with both salt concentrations. Vegetative, yield, and anatomical characters, leaf photosynthetic pigments, and grain crude protein declined in response to stress, while electrolyte leakage (EL), proline, glycine betaine (GB), total carbohydrates and antioxidant enzymes increased under same conditions. The maximum increments in vegetative characters were notable at concentrations of either AsA at 300 ppm or Put at 100 ppm. Yield characters were enhanced at 300 ppm AsA and both concentrations of Put. Improvement in anatomical features of leaf and stem was achieved with the combination of either AsA at 300 ppm or Put at 100 ppm with salinity at 14 dS m-1. AsA was more effective in enhancing photosynthetic pigments and crude protein individually or in combination with salinity. Combinations of either AsA or Put with salinity induced decrements in EL, GB and antioxidant enzymes and increments in proline and total carbohydrates. In conclusion, foliar application of AsA and Put could be considered an eco-friendly approach to alleviate the adverse effects of salinity on morphological and physiological characters of barley.